Pascamarxisme dan Dekonstruksi: Sebuah Percobaan Awal untuk Membaca Kontur Pascamarxisme dari Lensa “Heideggerian-Kiri” - Yulius Tandyanto (Dekonstruksi, 2021)
This article try to underscore a fertile possibility to relate the concept of “deconstruction” with postmarxism, insofar that the distinction between “the political” and “politics” could be traced to one of Heidegger’s key operative concepts, i.e. “Destruktion”. Within this optics I try to read Laclau-Mouffe’s criticism of historical materialism as a fruitful example of deconstruction that not only shows inadequacies of Marxian’s claims such as historical determinism, the priority of the proletariat, the dialectical teleology and the economic superiority, but also describes how both political theorists try to radicalize the concept of democracy. Therefore, the political could be understood as the contingent ground that deconstructs every rational order of politics.